Psychosocial Adaptation in a Sample of Students with Visual Disabilities in Mainstream and Regular Schools - Al- Hattab, Leen (Jordan Journal of Educational Sciences, 2015)
This study aims to find the differences between the merged visually impaired students who are in built-in schools and regular schools, according to their scores on the psychosocial adaption scale through dividing the study sample of (50) visually impaired students (8th, 9th and10th grades) into two groups; mixed in mainstream schools and visually impaired specialized schools in (2014/2015). The study also aimed to compare groups with psychosocial adaption according to the variables of sex and degree of disability, by applying psychosocial adaption at sample scale. The results showed a lack of statistically significant differences in the average scores of psychological and social adaption of students with visual impairment in the built-and the merged schools. The results also showed no statistically significant differences in psychological and social adaption of students with visual disabilities in mainstream schools in light of sex and degree of disability variables. Finally several recommendations have been proposed